1994
DOI: 10.1038/367645a0
|View full text |Cite
|
Sign up to set email alerts
|

A cell initiating human acute myeloid leukaemia after transplantation into SCID mice

Abstract: Most human acute myeloid leukaemia (AML) cells have limited proliferative capacity, suggesting that the leukaemic clone may be maintained by a rare population of stem cells. This putative leukaemic stem cell has not been characterized because the available in vitro assays can only detect progenitors with limited proliferative and replating potential. We have now identified an AML-initiating cell by transplantation into severe combined immune-deficient (SCID) mice. These cells homed to the bone marrow and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
3,121
6
45

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 4,235 publications
(3,300 citation statements)
references
References 19 publications
34
3,121
6
45
Order By: Relevance
“…The first evidence that a rare population of stem cells maintain the human cancer came from a study on haematopoietic malignancies (Lapidot et al, 1994). Haematopoietic malignancies can be divided into premalignant, chronic, and acute stages, the last being the most advanced and malignant.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…The first evidence that a rare population of stem cells maintain the human cancer came from a study on haematopoietic malignancies (Lapidot et al, 1994). Haematopoietic malignancies can be divided into premalignant, chronic, and acute stages, the last being the most advanced and malignant.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Consequently, McCulloch and colleagues postulated that AML can be considered as a clonal hemopathy [22,23]. However, the first prospective identification, characterization, and isolation of CSC/CICs was performed years later in AML on the basis of their phenotypical similarities to normal hematopoietic stem cells [24]; in their innovative work, Dick and colleagues have identified CD34 + CD38 − cells as AML CSCs [24,25]. Subsequently, the group reported that only CD34 + CD38 − cells were able to reproduce AML in recipient immunodeficient mice, which closely resembled the original patient's disease, and exhibited its full heterogeneous phenotype.…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
“…To date, the existence of CSCs has been proven in the context of many cancers, including those of leukemia, breast cancer, glioblastoma, prostate cancer, pancreatic cancer and colon cancer (Lapidot et al, 1994;Bonnet and Dick, 1997;Al-Hajj et al, 2003;Hemmati et al, 2003;Singh et al, 2003Singh et al, , 2004Collins et al, 2005;Ponti et al, 2005;Haraguchi et al, 2006;Patrawala et al, 2006;Li et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007). Recently, we have determined that HCC is hierarchically organized and originates from a primitive stem/progenitor group of cells for which CD133 þ precursors constitute one of the most immature stage (Ma et al, 2007).…”
mentioning
confidence: 99%